What makes a magnet? - Branley, Franklyn M. (Franklyn Mansfield), 1915-2002; DeCristofano, Carolyn Cinami (Let's-read-and-find-out science., 2016)
"How does a magnet work? Why does a magnet pick up a paper clip but not a leaf or a penny? How can the whole world be a magnet? Read and find out more about how magnets work! Franklyn M. Branley's classic text is seamlessly updated by NCTE Orbis Pictus Award Honoree Carolyn Cinami DeCristofano in this reissue. Now rebranded with a new cover look, this book features rich vocabulary, fascinating sidebars and diagrams by artist True Kelley, and a find-out-more section with a glossary and step-by-step instructions on how to make your own magnet and find magnetic technology in the world around you! This is a Level 2 Let's-Read-and-Find-Out Science title, which means the book explores more challenging concepts for children in the primary grades and supports the Common Core Learning Standards, Next Generation Science Standards, and the Science, Technology, Engineering, and Math (STEM) standards"--Publisher's description.